Aksentuasi Sosial, Ekonomi, Budaya dan Agama Masyarakat Bugis Dalam Pengembangan Kualitas Hidup di Kabupaten Jembrana Bali - Muhammad Habibi; I Wayan Subagiarta; Fajar Wahyu Prianto (UPT Penerbitan Universitas Jember, 2017)
Nowadays the quality of life as the priority issue for many countries and the quality of human’s life in generally has been usedto describe individual prosperous in society. This research purposes to find out the characteristic and the role of Bugis societytowords their quality of life in Jembrana regency which is connected to social, economics, culture and religion aspect. Theanalysis method which is used in this research is Participatori Rural Appraisal (PRA) method and Depth Interview method.From those result of analysis can be concluded that Loloan Bugis society has some changes. The changes happen to the social,economics, culture and religion value.